Molinism: Explaining our Freedom Away. Issue 522 (6th October 2021) - Climenhaga, Nevin; Rubio, Daniel
Abstract: Molinists hold that there are contingently true counterfactuals about what agents would do if put in specific circumstances, that God knows these prior to creation, and that God uses this knowledge in choosing how to create. In this essay we critique Molinism, arguing that if these theses were true, agents would not be free. Consider Eve's sinning upon being tempted by a serpent. We argue that if Molinism is true, then there is some set of facts that fully explains both Eve's action and everything else Eve does that influences that action; and that if this is the case, Eve does not act freely. The first premise of this argument follows from the explanatory relations the Molinist is committed to, and the second premise follows from libertarian intuitions about free will.